Research in finance. Vol. 28 - Kensinger, John W. (Emerald, 2012)
Contributions to Research in Finance, volume 28, include finance theory and financial practice, plus accounting issues such as reporting derivatives positions, reflecting intangible holdings, or predicting financial distress.
Keywords: Finance.; Investments.; elektronické knihy; electronic books